Nomenclatural corrections to two Neotropical species of Staphylininae (Coleoptera: Staphylinidae) - Márquez, Juan; Asiain, Julieta (Zootaxa, 2014)
Márquez & Asiain (2010) described three new species of the Philonthus furvus species group: P. navarretei and P. pollens from Mexico, and P. rufotibialis from Mexico and Guatemala. They also provided new state and locality records for P. hoegei, P. testaceipennis and P. yaqui, as well as a key for the identification of the species. In this work (Márquez & Asiain 2010) the depositories of the type material and material examined were indicated, except for the holotype of P. navarretei. Based on article 16 (names published after 1999) of the International Code of Zoological Nomenclature (International Commission on Zoological Nomenclature 1999), which indicates that species names must be accompanied by the explicit fixation of a holotype (16.4.1), a statement of intent that this will be deposited in a collection and a statement indicating the name and location of that collection (16.4.2), the species name is considered as an "unavailable name". Navarrete-Heredia & Newton (2013) placed P. navarretei Márquez & Asiain, 2010 as a nomen nudum because the term "nomen nudum" is often used loosely for names that do not meet one or more of the conditions necessary for availability in the International Code of Zoological Nomenclature.